Determinan Loyalitas Konsumen di Era Digital: Tinjauan Scoping tentang Transparansi Algoritma dan Ketahanan Konsumen terhadap Kelelahan Digital - Rubiyanti Rubiyanti; Alimatus Zahrah; Diah Cahyaningrum; Muhammad Fadly Fitrah Alghifari; Audita Nuvriasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the era of rapid digital transformation, the determinants of consumer loyalty are undergoing fundamental shifts. Two emerging factors of increasing significance are algorithmic transparency and digital fatigue resilience. Objective: This study aims to map the scientific evidence on the role of algorithmic transparency and digital fatigue as new determinants of consumer loyalty in the digital ecosystem. Methods: A scoping review was conducted following the Arksey and O’Malley (2005) framework updated by Levac et al. (2010), with PRISMA-ScR reporting (Tricco et al., 2018) using the PCC format. A protocol was developed before searches in Scopus (primary), Web of Science, and Google Scholar, period 2019–2025. A total of 9 articles met the inclusion criteria and were thematically analyzed. Results: Three major themes were identified: (1) algorithmic transparency as a mediator of digital trust (n=4); (2) digital fatigue as a moderator of engagement and loyalty (n=3); (3) the interaction between transparency and fatigue in shaping long-term loyalty behaviors (n=2). The review found that consumers exposed to clear algorithmic explanations demonstrated higher trust and loyalty, while high levels of digital fatigue weakened the relationship between personalization and loyalty. Conclusion: Algorithmic transparency and digital fatigue management are two critical determinants that need to be integrated into consumer retention strategies in the digital age.